2019
DOI: 10.1007/s11540-019-9417-4
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of miRNA and mRNA Targets in Potato Leaves Displaying Temperature-Dependent Responses to Potato Virus Y

Abstract: We demonstrate temporal-, spatial-and temperature-dependent expression of five host microRNAs and target mRNAs in potato leaves after potato virus Y (PVY) inoculation. A novel gene, Ny-DG, conferring resistance to PVY was mapped on chromosome IX in the diploid potato clone DG 81-68. At 20°C, the PVY NTN strain was localized in the inoculated leaves without symptoms. At 28°C, necrotic lesions were observed in both the inoculated leaves and the non-inoculated upper leaves and the virus spread systemically, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…Elevated expression of AGO1-2, DCL1 and stu-miR168a in the PVS-resistant cvs Tonacja and Tajfun but not in the susceptible cv. Bryza demonstrated in our present study, as well as their altered expression in PVY-resistant genotypes in previous studies (Szajko et al, 2019;, indicates their involvement in potato resistance to PVS and PVY. (h) Gpa2 (PGSC0003DMT400050510), disease resistance protein Gpa2; (i) stu-miR482_15854 (PotatoMir1005353123_x15854); (j) CC-NBS-LRR (PGSC0003DMT400019599), CC-NBS-LRR resistance protein, JHL06P13.14 protein.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Elevated expression of AGO1-2, DCL1 and stu-miR168a in the PVS-resistant cvs Tonacja and Tajfun but not in the susceptible cv. Bryza demonstrated in our present study, as well as their altered expression in PVY-resistant genotypes in previous studies (Szajko et al, 2019;, indicates their involvement in potato resistance to PVS and PVY. (h) Gpa2 (PGSC0003DMT400050510), disease resistance protein Gpa2; (i) stu-miR482_15854 (PotatoMir1005353123_x15854); (j) CC-NBS-LRR (PGSC0003DMT400019599), CC-NBS-LRR resistance protein, JHL06P13.14 protein.…”
Section: Discussionsupporting
confidence: 81%
“…Studies of host miRNAs in plant–virus interaction have been documented in 29 plant species and 12 DNA and 38 RNA virus species (Yin, 2021). In potato, changes in host miRNA expression in response to viral infection have been reported for two virus species, potato virus A (PVA) and potato virus Y (PVY) (Križnik et al, 2017; Li et al, 2017; Szajko et al, 2019; Yin et al, 2017). A total of 201 differentially expressed miRNAs were identified in the PVA‐hypersensitive potato A6 ( Solanum demissum × Aquila) following PVA infection (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ry hou gene was found in S. hougasii [78] but it has not been used for breeding. Additionally, the Ny-DG gene present in the diploid potato clone DG-68 features ER-like response [79]. Recently, a dominant resistant gene Ry(o) phu was identified in S. tuberosum ssp.…”
Section: Extreme Resistance Response: No Signs Of Battlementioning
confidence: 99%
“…Literature data contain evidence that miR162 regulates the DCL1 expression in other plants (Xie et al, 2003;Liu et al, 2014a;Szajko et al, 2019), whereas in yellow lupine, we have identified a new regulator of DCL2 (Glazinska et al, 2019), a novel miRNA named "Ll-miRn30, " deposited in the database under ID486.…”
Section: Analysis Of Mirnas That Target Dcl1 and Dcl2 In Yellow Lupinementioning
confidence: 99%